2021
DOI: 10.2188/jea.je20200018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trajectories of Suicide Attempts and Self-harm in Patients Admitted to Acute-care Hospitals in Japan: A Nationwide Inpatient Database Study

Abstract: Background: For patients with suicide attempts or self-harm, acute-care hospitals often function as the primary or sole point of contact with the healthcare system. However, little is known about patient characteristics or clinical trajectories of suicide attempts and self-harm episodes among those admitted to acute-care hospitals. This study aimed to describe the characteristics of suicide attempts and self-harm among patients admitted to acute-care hospitals, and the clinical practices provided in these hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The ED often functions as the entry point to the healthcare system for patients who have attempted suicide. [ 7 ] The current results suggest that this important function of the ED was significantly affected by a reduction in in-hospital psychiatric resources. The information presented herein should be considered by hospital administrators and policymakers, as well as by emergency and psychiatric health care providers.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The ED often functions as the entry point to the healthcare system for patients who have attempted suicide. [ 7 ] The current results suggest that this important function of the ED was significantly affected by a reduction in in-hospital psychiatric resources. The information presented herein should be considered by hospital administrators and policymakers, as well as by emergency and psychiatric health care providers.…”
Section: Discussionmentioning
confidence: 78%
“…Patients who have attempted suicide are a distinct demographic in the emergency department (ED). Because many suicide attempts and self-harm episodes result in ED visits, the ED often functions as the primary or sole point of contact with the healthcare system, [ 7 ] and serves as a safety net. In-house psychiatric resources such as suicide risk assessment provided by psychiatric consultants, close monitoring and care provided by psychiatric nurses, and in-house psychiatric wards that admit patients requiring emergency psychiatric care provide important back-up support for this particularly vulnerable patient population in ED.…”
Section: Introductionmentioning
confidence: 99%
“…Promoting timely access to mental health‐care and enhancing financial and social support could contribute to decrease the incidence of self‐harm 24 . Moreover, a previous study argued that many acute care hospitals in Japan were not able to provide appropriate psychiatric care for patients who engaged in self‐harm 25 . Initiating psychiatric care intervention in the emergency hospitals receiving these patients could help to improve patient care for those who visit the emergency department due to self‐harm.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a declining trend in suicide in recent years, the rate is still higher than the average among high-income Organization for Economic Co-operation and Development (OECD) nations [ 3 ]. One nationwide descriptive study using data on emergency hospital admissions in Japan showed that among patients, the most common method of unsuccessful suicide or self-harm attempts was drug overdose (50%), followed by hanging, jumping from a height, and cutting or piercing other than wrist cutting; [ 4 ] while for suicide deaths from 1979 to 2016 was majorly driven by hanging [ 5 ]. A study conducted in Akita prefecture have reported male predominance (73.9%) in completed suicides, and contrarily, a female predominance (59.1%) in failed attempts [ 6 ].…”
Section: Introductionmentioning
confidence: 99%